Колебательные свойства квазиодномерной наноструктурной решётки из аморфного кремния [Articol] - Крышмарь, Дмитрий (CEP USM, 2013)
În lucrare sunt efectuate cercetări teoretice privind determinarea stării cuantelor mişcării de vibraţie a atomilor în nanofirele din siliciu amorf. Au fost calculate relaţiile de dispersie la diferite grade de amorfizare a acestor structuri nanometrice cu dimensiuni de doar câteva monostraturi. Se arată că curbele densităţilor fononice, fiind în acord cu rezultatele experimentale, se schimbă semnificativ în nanofirele amorfe comparativ cu nanofirele cristaline. Se observă efectul micşorării puternice a vitezelor medii de grup ale transportului fononilor în nanofirele din siliciu amorf, fapt explicat prin cuantificarea dimensională a spectrului fononic din cauza dezordonării legăturilor atomice, care formează nanostructurile cvasiunidimensionale.

In this paper, a theoretical study has been conducted to determine the quantum states of the vibration motion of atoms in amorphous silicon nanowires. Dispersion dependencies were calculated at various degrees of amorphization of such nanometer structures with dimensions of only a few monolayers. It is shown that the curves of phonon densities are in agreement with experimental results and change significantly in amorphous nanowires as compared with crystalline nanowires. The effect of a strong drop in average group velocities of the phonon transport is observed in silicon amorphous nanowires, explained by size quantization of the phonon spectrum due to a disordering of atomic bonds that form quasione-dimensional nanostructures
PROPRIETĂŢILE VIBRAŢIONALE ALE REŢELEI CVASIUNIDIMENSIONALE NANOSTRUCTURATE DIN SILICIU AMORF
VIBRATIONAL PROPERTIES OF THE QUASI-ONE-DIMENSIONAL NANOSTRUCTURED LATTICE OF AMORPHOUS SILICON
Keywords: nanostructuri cvasiunidimensionale amorfe; modelul Valence Force Field; transport fononic; quasi-one-dimensional amorphous nanostructure; phonon transport